¿Cómo financiar la guerra? El sistema fiscal en la administración bonapartista en Guipúzcoa durante la Guerra de la Independencia - Gárate Ojanguren, Mª Montserrat (Boletín de la Real Sociedad Bascongada de Amigos del País, 2008)
The French were already present in Guipuzcoa before war was declared. Likewise, they stayed in the territory for more than six years. During this time, the invaders tried to set up their own administrative and fiscal system. From January 1809, changes were introduced in the courts of commerce, justice, police etc. Once the new institutions were established, Guipuzcoa became part of the Province of Biscay, under the command of General Thouvenot, who, in February 1810, took on responsibility for all civil, military, economic and justice matters. A few days later, the General named the representatives of the provincial council, all very important people in the socio-political life of Guipuzcoa. At the same time as these changes were being introduced, the French devoted their time to raising funds to pay for the cost of the war and maintain the new administration. The attempt to set up an ordered tax system did not work faced with the urgent needs they had to meet in an extraordinary way by means of loans and requisitions.